The Agha residence at the archaeological palace of Taouiala in Algeria(its history and its artistic and architectural characteristics) - Salim, Guebboub Lakhdar; Dahmani, Malika (Journal of Humanities & Social Sciences, 2019)
This study is part of the rehabilitation and enhancement of the Taouiala palace of the Laghouat in the Sahara desert of Algeria, addressing its various historical and artistic values. In this research, we focused on Abzar, the most important features of housing, particularly as regards the type of construction and local materials used in construction, trying to minimize even a small definition of the heritage, customs and social fabric of the region. On the other hand, this palace has not been spared a set of damage factors which have masked its true natural and human image, as well as biological and chemical in a direct and indirect way, leaving and saw its remarkable effects in the form of scattered ruins disappear and disappear. That is why we must propose a set of measures to preserve and preserve it, to remain a witness and an archaeological heritage throughout the history and past of a generation that has made its children an archaeological artistic value and a tourist destination that abounds with people and the country in general.